LATP-containing high-nickel ternary positive electrode material and preparation method thereof

By uniformly distributing LATP water nanoslurry in high-nickel ternary cathode material, and preparing and forming a gel state by sol-gel method, the problem of degradation of thermal safety performance of high-nickel ternary cathode materials in the prior art is solved, and good lithium ion conduction path and significantly enhanced thermal safety are achieved.

CN119764387AActive Publication Date: 2025-04-04CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411946555.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

While the existing high-nickel ternary cathode materials increase the specific energy, the thermal safety performance decreases, and the LATP solid electrolyte is unevenly coated, resulting in limited lithium ion conduction and unable to fully improve the electrochemical performance and thermal safety.

Method used

By uniformly distributing LATP aqueous nanoslurry in high nickel ternary positive electrode material, a gel state is prepared by sol-gel method, followed by drying and sintering, the material structure is optimized to improve lithium ion conduction path and thermal safety.

Benefits of technology

The good lithium ion conduction path and significantly enhanced thermal safety of high-nickel ternary cathode materials are achieved, and the overall electrochemical performance of lithium ion batteries and the stability in high temperature environment are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764387A_ABST
    Figure CN119764387A_ABST
Patent Text Reader

Abstract

The invention relates to an LATP-containing high-nickel ternary positive electrode material and a preparation method thereof.LATP aqueous nano slurry with the particle size distribution ranging from 70 nm to 100 nm serves as one of raw materials for preparing the high-nickel ternary positive electrode material, uniform compounding of nano LATP and the high-nickel ternary material is achieved in the sol-gel process, and then drying and sintering are conducted to obtain the high-nickel ternary positive electrode material containing LATP. The powder material can be used as a positive electrode slurry active substance; the electrochemical performance and the thermal safety of the high-nickel ternary positive electrode material are improved by uniformly mixing LATP into the high-nickel ternary material, and the thermal safety of a battery can be remarkably improved after the high-nickel ternary positive electrode material is used for a battery positive electrode or further used for a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a high-nickel ternary positive electrode material containing LATP and a preparation method thereof. Background Art

[0002] With the continuous development of science and technology today, facing the global energy crisis, traditional fossil energy is facing depletion and bringing environmental pollution and greenhouse gas emissions. Many countries and regions have introduced policies to support the development of new energy vehicles and lithium-ion batteries. Continuous investment in scientific research has continuously improved the energy density of lithium-ion batteries, extended the cycle life, and automated production lines have reduced manufacturing costs and improved reliability. The improvement in cost-effectiveness has accelerated the widespread application of lithium-ion batteries in various fields, such as electric vehicles, energy storage systems, portable electronic devices and special fields.

[0003] Against the background of the continuous scale progress of lithium-ion batteries, the market environment has also put forward higher technical requirements for lithium-ion batteries. The biggest contradiction at present is the balance between the improvement of lithium-ion battery specific energy and the guarantee of thermal safety performance. The market demands batteries with higher capacity and energy, smaller volume, lighter weight, and better charge and discharge performance. The positive electrode materials have evolved from lithium iron phosphate system to lithium cobalt oxide system and ternary system, and then to 8 series and 9 series ternary system. While the specific energy has increased, the safety performance has decreased. The issue of thermal safety of lithium-ion batteries has attracted more and more attention. Therefore, it is of great significance to develop high-nickel ternary positive electrode materials with higher specific energy and thermal safety performance. Existing inventions usually coat a layer of LATP solid electrolyte on the surface of high-nickel ternary positive electrode materials. However, this method generally has the problem of uneven coating, which leads to limited lithium ion conduction in local areas of the pole piece and cannot fully improve the overall electrochemical performance and thermal safety. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a high-nickel ternary positive electrode material containing LATP and a preparation method thereof.

[0005] The technical solution adopted by the present invention is: a method for preparing a high-nickel ternary positive electrode material containing LATP, comprising the following steps:

[0006] Step 1: dissolve the nickel source, cobalt source, manganese source or aluminum source and lithium source in water, add the complexing agent and LATP aqueous nano slurry, and mix them evenly;

[0007] Step 2: Continuously stirring the mixture under heating conditions until a gel is formed;

[0008] Step 3: Dry the gel, sinter it at 80-200°C and grind it into powder;

[0009] Step 4: Sinter the powder at 300-600°C to obtain a high-nickel ternary positive electrode material containing LATP.

[0010] Preferably, the molar ratio of lithium:nickel:cobalt:manganese or aluminum is 1.03:0.5:0.2:0.3 to 1.05:0.9:0.05:0.05.

[0011] Preferably, step one is also doped with magnesium salt and / or titanium salt.

[0012] Preferably, the metal salt is a mixture of one or more of sulfate, nitrate and chloride.

[0013] Preferably, the complexing agent is one or more of citric acid, EDTA and ammonia water, and the added amount is 1 to 2 times the total molar number of metal ions.

[0014] Preferably, the particle size of the LATP aqueous slurry is 70-100 nm, and the mass of LATP is 0.5%-2% of the mass of the high-nickel ternary positive electrode material.

[0015] Preferably, the heating temperature in step 2 is 60-100°C.

[0016] The invention discloses a method for preparing a high-nickel ternary positive electrode material containing LATP and obtains a high-nickel ternary positive electrode material containing LATP.

[0017] A battery positive electrode is prepared from a positive electrode slurry comprising a high-nickel ternary positive electrode material containing LATP.

[0018] A lithium-ion battery includes a positive electrode.

[0019] The advantages and positive effects of the present invention are as follows: the prepared positive electrode material has a good lithium ion conduction path, and its intrinsic thermal safety is also significantly enhanced. The positive electrode material is prepared to form a lithium ion battery, which can improve the thermal safety of the lithium ion battery. In addition, the positive electrode material is prepared by the method of the present invention, and the doping method of each element is simple and effective, and the mixing is uniform; the main metal elements Ni, Co, Mn, and Li are evenly distributed, and the preparation is simple and easy, and no additional Li source sintering is required, thereby optimizing the preparation steps.

[0020] The components in the positive electrode material are mixed at the nanoscale, and have a more evenly distributed LATP component compared to conventional coating methods; the evenly distributed LATP component provides a continuous and efficient lithium ion transmission channel, enhances the stability of the material working in a high-temperature environment, and reduces the safety risks caused by increased temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 SEM image of the high-nickel ternary positive electrode material containing LATP prepared in Example 1. DETAILED DESCRIPTION

[0022] The embodiments of the present invention are described below with reference to the accompanying drawings.

[0023] The invention relates to a high-nickel ternary cathode material containing LATP and a preparation method thereof. LATP aqueous nano slurry with a particle size distribution of 70nm to 100nm is used as one of the raw materials for preparing the high-nickel ternary cathode material, and uniform compounding of nano LATP and the high-nickel ternary material is achieved in a sol-gel process, thereby improving the electrochemical performance and thermal safety of the high-nickel ternary cathode material.

[0024] During the preparation, nickel source, cobalt source, manganese source or aluminum source are mixed, and metal salts such as magnesium and titanium can also be doped as needed, mixed with a complexing agent, and then LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) Aqueous nano-slurry is prepared by sol-gel method to form a gel state, and then the gel material is dried and sintered to obtain the active ingredient for preparing the positive electrode slurry; through uniform mixing of the solution level, LATP is uniformly compounded in the ternary material. Further, the active ingredient can be prepared into a lithium-ion battery positive electrode, and then assembled to form a lithium-ion battery. Through testing, it is found that the prepared lithium-ion battery has excellent thermal safety.

[0025] The specific preparation method of the high nickel ternary cathode material containing LATP is as follows:

[0026] Step 1: dissolving a metal salt such as a nickel source, a cobalt source, a manganese source or an aluminum source and a lithium source in deionized water to form a uniform mixed solution; in certain embodiments of the present invention, a doping element in the form of a metal salt such as a magnesium salt or a titanium source may also be added; then adding a complexing agent citric acid in an amount of 1 to 2 times the total molar number of metal ions in the solution to prevent metal ion precipitation, adding LATP aqueous nano slurry to the solution so that the mass of LATP accounts for 0.5% to 2% of the mass of the high-nickel ternary positive electrode material; and fully stirring the mixed solution to mix it evenly;

[0027] The metal salt is a metal salt of nickel source, cobalt source, manganese source or aluminum source, and can be one or more of sulfate, nitrate, and chloride; the complexing agent is one or more of citric acid, EDTA or ammonia water; the particle size of the LATP aqueous slurry is 70nm to 100nm; the molar ratio of lithium: nickel: cobalt: manganese (aluminum) is 1.03: 0.5: 0.2: 0.3 to 1.05: 0.9: 0.05: 0.05

[0028] Step 2: Continue stirring the mixture at 60°C to 100°C to promote good combination of LATP and other components, so that the mixture gradually turns into a transparent sol state, and continue heating until the sol turns into a gel and then stop heating;

[0029] Step 3: The formed gel is placed in an oven at 60°C to 100°C for drying to remove excess moisture. The dried gel undergoes preliminary low-temperature pre-sintering at a temperature range of 80°C to 200°C to remove volatile and low-temperature decomposable substances in the gel, avoid the appearance of a large number of pore structures inside the material, and make the material initially densified. After sintering, the material is ground into powder and sieved;

[0030] Step 4: The powder is sintered at a high temperature of 300°C to 600°C to further improve the density of the material and optimize the crystal structure. After screening, a high-nickel ternary positive electrode material containing LATP with excellent structural properties is obtained.

[0031] Through the above preparation process, a high-nickel ternary positive electrode material with LATP evenly distributed inside the material can be prepared, which has a good lithium ion conduction path and its intrinsic thermal safety has also been significantly enhanced. It can be used as an active ingredient in the positive electrode slurry. There is no need to add lithium salt to the positive electrode slurry. The nickel ternary positive electrode material is directly mixed with a conductive agent and a binder to prepare a positive electrode slurry, which can be further prepared to form a battery positive electrode. The components in the positive electrode material are mixed at the nanoscale, and compared with conventional coating methods, the LATP component is more evenly distributed; the evenly distributed LATP component provides a continuous and efficient lithium ion transmission channel, which enhances the stability of the material in high temperature environments and reduces safety risks caused by increased temperature.

[0032] The present invention is described below in conjunction with the accompanying drawings, wherein the experimental method of the operating steps is not specifically described, all according to the corresponding product specifications, and the instruments, reagents, and consumables used in the embodiments can be purchased from commercial companies unless otherwise specified. All raw materials of the present invention are not particularly limited to their sources, and can be prepared according to conventional methods well known to those skilled in the art purchased on the market. All raw materials of the present invention are not particularly limited to their purity, and the present invention preferably uses analytically pure or conventional purity in the field of lithium ion batteries.

[0033] Embodiment 1:

[0034] Dissolve nickel chloride, cobalt chloride, manganese chloride and lithium chloride in water, wherein lithium: nickel: cobalt: manganese are added in a molar ratio of 1.05: 0.8: 0.1: 0.1; add citric acid 1.2 times the total molar number of metal ions to the solution and stir to dissolve, then add 1% of the mass of the ternary material LATP aqueous nano slurry (average particle size 70nm-100nm), stir and mix the mixture thoroughly. Continue stirring under heating conditions of 80°C to promote good combination of LATP and other components, so that the mixture gradually turns into a transparent sol state; continue heating at 80°C until the sol turns into a gel and then stop heating.

[0035] The prepared gel was placed in an oven at 80°C for drying to remove excess water. The dried gel was ground into powder, and then pre-sintered at 150°C for 3 hours and passed through a 200-mesh sieve. The obtained powder was then sintered at 550°C for 12 hours and passed through a 200-mesh sieve to obtain a high-nickel ternary cathode material with excellent structural properties, in which LATP was evenly distributed inside the material. The microstructure of the prepared high-nickel ternary cathode material containing LATP was observed, and its SEM image is shown below. Figure 1 As shown, the overall particles are relatively evenly distributed, have certain agglomeration phenomena, irregular morphology, and rough surface.

[0036] Embodiment 2:

[0037] Dissolve nickel chloride, cobalt chloride, aluminum chloride and lithium chloride in water, wherein lithium: nickel: cobalt: aluminum are added in a molar ratio of 1.05: 0.8: 0.1: 0.1; add citric acid twice the total molar number of metal ions to the solution and stir to dissolve, then add 0.5% of the mass of the ternary material LATP aqueous nano slurry (average particle size 70nm-100nm), stir and mix the mixture thoroughly. Continue stirring at 80°C to promote good combination of LATP and other components, so that the mixture gradually turns into a transparent sol state; continue heating at 80°C until the sol turns into a gel and then stop heating.

[0038] The prepared gel was placed in an oven at 80°C for drying to remove excess water, and the dried gel was ground into powder, and then pre-sintered at 200°C for 2 hours, and passed through a 200-mesh sieve. The obtained powder was then sintered at 550°C for 12 hours, and passed through a 200-mesh sieve to obtain a high-nickel ternary positive electrode material containing LATP with excellent structural properties, in which LATP is evenly distributed inside the material.

[0039] Embodiment 3:

[0040] Nickel chloride, cobalt chloride, aluminum chloride, lithium chloride, magnesium chloride and titanium chloride are dissolved in water, wherein lithium: nickel: cobalt: aluminum: magnesium: titanium are added in a molar ratio of 1.05: 0.8: 0.1: 0.1: 0.05: 0.05; 1.2 times the total molar number of metal ions of citric acid are added to the solution and fully stirred to dissolve; then 1% of the mass of the ternary material LATP aqueous nano slurry (average particle size 70nm ~ 100nm) is added, and the mixed solution is fully stirred and mixed evenly.

[0041] The mixture was stirred continuously at 80°C to promote good combination of LATP and other components, so that the mixture gradually turned into a transparent sol state; heating was continued at 80°C until the sol turned into a gel and then the heating was stopped.

[0042] The prepared gel was placed in an oven at 80°C for drying to remove excess water, and the dried gel was ground into powder, and then pre-sintered at 200°C for 2 hours, and passed through a 200-mesh sieve. The obtained powder was then sintered at 550°C for 12 hours, and passed through a 200-mesh sieve to obtain a high-nickel ternary positive electrode material containing LATP with excellent structural properties, in which LATP is evenly distributed inside the material.

[0043] Embodiment 4:

[0044] The high-nickel ternary positive electrode material containing LATP prepared in Example 1 was mixed with the conductive agent CNT and the binder PVDF in a NMP solution at a mass ratio of 97:1:2, and stirred at a high speed of 2500 rpm for 3 hours to obtain a lithium battery positive electrode slurry.

[0045] The prepared positive electrode slurry was coated on aluminum foil and dried to obtain a positive electrode sheet. The positive electrode sheet, graphite negative electrode (graphite: conductive agent: binder = 96:2:2) and separator were stacked, packaged, baked, injected, remotely sealed, left to stand, formed, degassed and directly sealed, capacity divided, and aged to produce a 20Ah-class battery 1, which was tested. The test results are shown in Table 1.

[0046] Embodiment 5:

[0047] The high-nickel ternary positive electrode material containing LATP prepared in Example 1 was mixed with the conductive agent CNT and the binder PVDF in a NMP solution at a mass ratio of 97:1:2, and stirred at a high speed of 2500 rpm for 3 hours to obtain a lithium battery positive electrode slurry.

[0048] The positive electrode slurry is coated on aluminum foil and dried to obtain a positive electrode sheet. The obtained positive electrode sheet, carbon silicon negative electrode (graphite: silicon: conductive agent: binder = 94:2:2:2) and separator are stacked, packaged, baked, injected with liquid, packaged, allowed to stand, formed, and capacity divided to make a 20Ah-class battery 2, which is tested. The test results are shown in Table 1.

[0049] Embodiment 6:

[0050] The high nickel ternary positive electrode material containing LATP prepared in Preparation Example 1 was mixed with the conductive agent CNT and the binder PVDF in a NMP solution at a mass ratio of 97:1:2, and stirred at a high speed of 2500 rpm for 3 hours to obtain a positive electrode slurry.

[0051] The positive electrode slurry was coated on aluminum foil and dried to obtain a positive electrode sheet. The positive electrode sheet, graphite negative electrode (graphite: silicon: conductive agent: binder = 88:8:2:2) and separator were stacked, packaged, baked, injected, packaged, allowed to stand, formed, and capacity divided to produce a 20Ah-class battery 3, which was tested. The test results are shown in Table 1.

[0052] Embodiment 7:

[0053] The high-nickel ternary positive electrode material containing LATP prepared in Example 2 was mixed with the conductive agent CNT and the binder PVDF in a NMP solution at a mass ratio of 97:1:2, and stirred at a high speed of 2500 rpm for 3 hours to obtain a positive electrode slurry.

[0054] The positive electrode slurry is coated on aluminum foil and dried to obtain a positive electrode sheet. The positive electrode sheet, graphite negative electrode (graphite: silicon: conductive agent: binder = 88:8:2:2) and separator are stacked, packaged, baked, injected, packaged, allowed to stand, formed, and capacity divided to produce a 20Ah-class battery 4, which is tested. The test results are shown in Table 1.

[0055] Embodiment 8:

[0056] The high-nickel ternary positive electrode material containing LATP prepared in Example 3 was mixed with the conductive agent CNT and the binder PVDF in a NMP solution at a mass ratio of 97:1:2, and stirred at a high speed of 2500 rpm for 3 hours to obtain a positive electrode slurry.

[0057] The positive electrode slurry was coated on aluminum foil and dried to obtain a positive electrode sheet. The positive electrode sheet, graphite negative electrode (graphite: silicon: conductive agent: binder = 88:8:2:2) and diaphragm were stacked, packaged, baked, injected, packaged, allowed to stand, formed, and capacity divided to produce a 20Ah-class battery 5, which was tested. The test results are shown in Table 1.

[0058] Comparative Example 1:

[0059] The LATP slurry, conductive agent CNT, and binder PVDF were first mixed evenly in NMP solution, and then NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2) materials, the total mass of which is mixed according to the ratio of positive electrode material: LATP: conductive agent: binder = 96.5:0.5:1:2, and then stirred at a high speed of 2500 rpm for 3 hours to obtain positive electrode slurry.

[0060] The positive electrode slurry is coated on aluminum foil and dried to obtain a positive electrode sheet. The positive electrode sheet, graphite negative electrode (graphite: silicon: conductive agent: binder = 88:8:2:2) and diaphragm are stacked, packaged, baked, injected, packaged, allowed to stand, formed, and capacity divided to produce a 20Ah-class battery 6, which is tested. The test results are shown in Table 1.

[0061] Battery performance test

[0062] The batteries obtained in each embodiment and comparative example were tested, and the test items and steps are as follows:

[0063] 1) Specific energy: 0.2C charge and discharge at 25℃.

[0064] 2) Needle penetration test: When the battery is fully charged (100% SOC), a needle with a diameter of 3mm and a taper of

[0065] The 30° steel needle pierced the battery radially at a speed of 40 mm / s, and the steel needle stayed in the battery for 1 h.

[0066] 3) Extrusion test: A fully charged battery is placed between two steel plates of a press. Starting from the initial contact point, it is squeezed at an initial speed of about 1.5 cm / s until the pressure is not less than 13 kN or the voltage of the sample drops to less than 2 / 3 of the original.

[0067] Table 1 Battery test results

[0068]

[0069]

[0070] Among them, n / 10 means that n samples out of 10 battery samples in each batch passed the test.

[0071] By comparing batteries 1-3 and battery 6 prepared in comparative example 1, it can be seen that more uniform addition of LATP can effectively improve the safety of lithium-ion batteries and increase the probability of battery overcharge, extrusion and puncture.

[0072] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a high-nickel ternary positive electrode material containing LATP, characterized in that: The steps include: Step 1: dissolve the nickel source, cobalt source, manganese source or aluminum source and lithium source in water, add the complexing agent and LATP aqueous nano slurry, and mix well; Step 2: Continuously stirring the mixture under heating conditions until a gel is formed; Step 3: Dry the gel at 80-200°C and grind it into powder; Step 4: Sinter the powder at 300-600° C. to obtain a high-nickel ternary positive electrode material prepared from LATP aqueous nano-slurry.

2. The method for preparing the high-nickel ternary positive electrode material containing LATP according to claim 1, It is characterized by: lithium: The molar ratio of nickel:cobalt:manganese or aluminum is 1.03:0.5:0.2:0.3 to 1.05:0.9:0.05:0.

05.

3. The method for preparing a high-nickel ternary positive electrode material containing LATP according to claim 1, characterized in that: Step one is also doped with magnesium salt and / or titanium salt.

4. The method for preparing a high-nickel ternary positive electrode material containing LATP according to claim 1 or 3, characterized in that: The metal salt is a mixture of one or more of sulfate, nitrate and chloride.

5. The method for preparing a high-nickel ternary positive electrode material containing LATP according to claim 1, characterized in that: The complexing agent is one or more of citric acid, EDTA and ammonia water, and the added amount is 1 to 2 times the total molar number of metal ions.

6. The method for preparing a high-nickel ternary positive electrode material containing LATP according to claim 1, characterized in that: The particle size of the LATP aqueous slurry is 70 to 100 nm, and the mass of the LATP is 0.5% to 2% of the mass of the high-nickel ternary positive electrode material.

7. The method for preparing a high-nickel ternary positive electrode material containing LATP according to claim 1, characterized in that: The heating temperature in step 2 is 60-100°C.

8. The high-nickel ternary positive electrode material containing LATP obtained by the preparation method of the high-nickel ternary positive electrode material containing LATP according to any one of claims 1 to 7.

9. A positive electrode of a battery, characterized in that: The method is prepared from a positive electrode slurry comprising the high-nickel ternary positive electrode material containing LATP as described in claim 8.

10. A lithium ion battery, characterized in that: The battery positive electrode comprises the battery positive electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Lanthanum and magnesium doped high-nickel ternary lithium battery positive electrode material and preparation method

    CN108550822A

  • LATP / high-nickel composite positive electrode material, positive plate and battery

    CN114551819A

  • Double-coated high-nickel lithium ion positive electrode material as well as preparation method and application thereof

    CN116487553A

  • Positive plate for high-rate, long-cycle and high-safety lithium battery as well as preparation method and application of positive plate

    CN116565141A

  • Solid electrolyte integrated composite modified positive electrode material and application thereof in battery

    CN119050324A